Employee Retention Aligns with Training Culture and Work Life Balance: Retensi Karyawan Selaras Dengan Pelatihan Budaya dan Work Life Balance - Indah Aufiyah; Made Dwipa Negara; Komang Sudarsana (Indonesian Journal of Law and Economics Review, 2026)
General Background: Employee retention is essential for maintaining workforce stability and organizational sustainability. Specific Background: This study examines permanent employees in a seafood processing company with physically demanding work characteristics. Knowledge Gap: Prior studies mostly examined job training, organizational culture, and work-life balance separately or in different sectors. Aims: This study analyzes the partial and simultaneous relationships between job training, organizational culture, work-life balance, and employee retention. Results: Using questionnaires from 32 permanent employees and multiple linear regression, the findings show that job training, organizational culture, and work-life balance have positive and significant relationships with employee retention, both partially and simultaneously. Novelty: This study integrates three human resource factors in a seafood processing work context. Implications: Companies should strengthen training, supportive culture, and balanced work arrangements to maintain employee loyalty and long-term retention. Highlights• Job training supports employee loyalty through improved competence and confidence.• Organizational culture creates a comfortable workplace through teamwork and communication.• Balanced work arrangements reduce fatigue and support longer employee commitment. KeywordsEmployee Retention; Job Training; Organizational Culture; Work Life Balance; Human Resource Management